(3GdJjSjQ aj GdbQGAGJ GdSHYs - (3YKeGf Hf SYjO Hf YKeGf, CHh YeQh GdOGfj , GHf GdUjQaj,J (B444 (3g` s ((3CMeO Hf CHj HcQ Hf CMeO Gdeci s)
(3ChdgG (B:s
(3GdMeO ddg GdefaQO HGdOhGe CeG HYO , aEfce SCdJehfi CMSf Gddg EQTGOce Cf CUfa dce cJGHkG eNJUQkG ai ePGgH GdbQGA GdSHYI s
(3BNQgG (B:s
(3BNQg ai (B" (3HGH PcQ GdJcHjQ (B" (3bhdg (B: (3hGSbWJ Cda GdhUd GdJi ai Chd GSe Gddg YR hLd ai LejY Pdc ESJZfGkA YfgG , aGYde Pdc ehabkG dWQjb GdMb hefgGL GdUhGH Je cJGH GdJjSjQ s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3Ydi MhGTjgG ebGHdGJs
(3cJHJ GdYfGhjjf hHYV GdcdeGJ HGdMeQI s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
Keywords: (3GdbQGAGJ hGdJLhjOs